2010
DOI: 10.1002/jcla.20368
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity and cardiovascular risk: baseline observations from men and premenopausal women

Abstract: These results suggest intrinsic sex differences between men and women in relation to atherogenic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
6
0
3
Order By: Relevance
“…In the available literature there are inconsistencies concerning the association between PA and biomarkers of oxidative stress and inflammation. Some authors [ 31 ] showed an inverse relationship between PA and blood ox-LDL levels, while others failed to document any correlations or significant results were limited to selected populations [ 32 , 33 ]. In our study we have not found an inverse relationship between lifetime LTPA level and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature there are inconsistencies concerning the association between PA and biomarkers of oxidative stress and inflammation. Some authors [ 31 ] showed an inverse relationship between PA and blood ox-LDL levels, while others failed to document any correlations or significant results were limited to selected populations [ 32 , 33 ]. In our study we have not found an inverse relationship between lifetime LTPA level and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Until the 1960s, absolute rest was recommended for patients with autoimmune rheumatic diseases to help treat the disease [5]. However, this recommendation has changed because sedentary behavior is now known to be associated with increases in triglyceride levels, blood pressure, insulin resistance, and cardiovascular risk [6,7]. In this context, exercise training emerged as a nonpharmacological therapy for patients with SAMs, thereby contributing to the restoration of the muscle strength and functional capacity of these individuals and improving their clinical condition.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent results also exist in strength-based training programs with some failing to achieve changes in blood lipid profile in postmenopausal women [ 17 , 18 ] or in adult men [ 16 ], while others have reported benefits [ 19 ]. Additionally, some studies focusing on the effects of the gender in the lipid profile have found significant differences, with women having higher HDL-C, decreased LDL-C, and decreased TG comparing with men [ 20 ]. High-sensitivy C-reactive protein (hs-CRP) is known to be a sensitive marker of inflammation and has also been related to increased risk of vascular disease [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%